JOURNAL OF GOVERNMENT & POLITICS : The Implications of Traditional Market Development for Governance of Conflicts : an Experience from Klewer Market of Surakarta, Indonesia - Sudarmo (FISIPOL UMY, 2016)
Klewer market has been developing since over six decades ago. Since the beginning of its development, conflicts among stakeholders in the market have repeatedly happened.